2023
DOI: 10.15251/cl.2023.201.63
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of manganese-doped FeS2 thin films via chemical spray pyrolysis

Abstract: A thin film of iron disulfide (FeS2) and Mn-doped was prepared using the chemical spray pyrolysis (CSP) method at a constant temperature of the glass substrate at around 400 °C. According to XRD examination, films were structurally cubic oriented with a predominant planar orientation (201). The doping of Mn ions in the FeS2 host matrix was confirmed by a minor shift of the diffraction peak towards the lower 2θ values. The surface of the produced film for pyrite was homogeneous, according to the AFM investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Since the dispersion energy depends on the optical transition and the optical conductivity, the refractive index (n) is a crucial element in fabricating devices with desirable optical properties. [42]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the dispersion energy depends on the optical transition and the optical conductivity, the refractive index (n) is a crucial element in fabricating devices with desirable optical properties. [42]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because MgS has a wider band gap than ZnS (3.72 eV), the Mg dopant can also enlarge the band gap in ZnS QDs. 45–47 In nanocrystalline Zn 1− x Mg x O thin films, Sandeep et al found that by altering the Mg content, the optical energy gap could be adjusted between 3.40–3.83 eV. For applications like optical windows and transparent conducting oxides in the UV spectral range, Zn 1− x Mg x O is a viable contender.…”
Section: Non-transition Element-doped Znsmentioning
confidence: 99%
“…When doped with 3 percent Mg, the film's transmittance reduced to 65 percent. The decrease in transmittance may be due to the successful integration of dopant atoms into the ZnS lattice [36,37].…”
Section: Optical Propertiesmentioning
confidence: 99%